2019
DOI: 10.1038/s41598-019-45400-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic and photosynthetic responses of big sagebrush to the 2017 total solar eclipse

Abstract: The total solar eclipse of August 21, 2017 created a path of totality ~115 km in width across the United States. While eclipse observations have shown distinct responses in animal behavior often emulating nocturnal behavior, the influence of eclipses on plant physiology are less understood. We investigated physiological perturbations due to rapid changes of sunlight and air temperature in big sagebrush ( Artemisia tridentata ssp. vaseyana ), a desert shrub common w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 89 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Photosynthesis is a key process for plants that is directly related to carbon balance and, in turn, to fitness and overall performance [21][22][23]. These responses may be associated with limitations in light quantity, but also with the quality of the solar eclipse light [5]. During a total eclipse, all wavelengths are reduced, but blue and UV wavelengths are reduced less than red and far-red (FR) wavelengths [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Photosynthesis is a key process for plants that is directly related to carbon balance and, in turn, to fitness and overall performance [21][22][23]. These responses may be associated with limitations in light quantity, but also with the quality of the solar eclipse light [5]. During a total eclipse, all wavelengths are reduced, but blue and UV wavelengths are reduced less than red and far-red (FR) wavelengths [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Variations in temperature and incoming radiation are considered primary drivers of photosynthetic processes and, in turn, carbon balance [4]. A recent study showed that rapid changes Forests 2021, 12, 1353 2 of 8 in sunlight and air temperature during a total solar eclipse on 21 August 2017, in the USA negatively impacted photosynthesis in Artemisia tridentata [5]. Furthermore, solar eclipses represent natural and unexpected events for plants [5] that can potentially affect photosynthetic performance at the individual level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heightened tendencies of individuals to form collectives by huddling, gathering and synchronising group movements during solar eclipses are also seen across several animal groups, terrestrial and aquatic alike (7). If solar eclipses play such a vital role in shaping individuals and their groups to ensure collective survival across species, it is remarkable that very little is known about how plants respond to these astronomical events and such knowledge is limited to responses at the individual level (8)(9)(10)(11)(12)(13)(14) overlooking that group behaviour has also been observed in plants (15,16). Here, we use a remote measurement system we have developed to simultaneously monitor multiple trees in a forest (17) to directly test whether individual trees respond to a solar eclipse together as a larger living collective, the forest.…”
Section: Main Textmentioning
confidence: 99%